EVALUATING THE EFFECTIVENESS OF HAND FUNCTION OF HEMIPLEGIA PATIENTS DUE TO CEREBRAL INFARCTION TREATED WITH ELECTROACUPUNCTURE COMBINED WITH CIMT EXERCISES (Vietnam Journal of Community Medicine, 2024)
Objectives: To describe the changes in hand function of hemiplegia patients due to cerebralinfarction and evaluate the effects of restoring hand function by electroacupuncture combined withCIMT exercises. Subjects and methods: a controlled clinical intervention on 84 patients diagnosedwith hemiplegia due to cerebral infarction patients at the National Hospital of Acupuncture. Results:100% of the studied patients had a change in motor function of the paralyzed hand, in which thefrequency of loss of opposed the thumb with fingers is the highest, 94.05%. Electroacupuncturecombined with CIMT exercises improves the hand function and dexterity of the paralyzed hand betterthan the group only treated by electroacupuncture (p
Keywords: Hemiplegia due to cerebral infarction, hand function, electroacupuncture, CIMT exercise.